The Implementation of Traditional Recitation As a Resource of Character Education Community of Siulak Village, Kerinci Regency - Eka Putra; Yuserizal Bustami (Universitas Pahlawan Tuanku Tambusai, 2023)
This research was aimed to find out and analyze how the implementation of traditional recitation activities as a resource of Character Education for the Siulak Mukai Community. Character education are coming from family and the surrounding environment is the main foundation for influencing human character. This traditional recitation activity is a program of the Siulak Mukai homegrown people. The purpose of the implementation of this traditional recitation activity was to start from the anxiety of the Siulak Mukai Village Community about the character of the children in Siulak Mukai who have begun to show the character and the personality that are not in agreement with Islamic religious values. This study shows that the main cause was the lack of religious activities carried out both recitation, and other religious events. Therefore, to disentangle this problems, traditional Quran recitation activities for children and young people in Siulak Mukai village were carried out. The type of this research was descriptive qualitative. Besides, the data was collected by using observation, interviews and documentation, then the data was analyzed by using the Milles & Huberman model, such as: data reduction, data display and conclusion drawing. The results of this research showed that: (1) The process of implementation or implementation of traditional recitation activities in Siulak Mukai must be carried out continuously and also structured (2) The character values instilled in traditional recitation activities are responsibility, tolerance, discipline, honesty and courtesy.